2022
DOI: 10.3390/en15228584
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic Response and Tension Leg Failure Performance Analysis of Floating Offshore Wind Turbine with Inclined Tension Legs

Abstract: The tension legs are the essential parts of the tension legs platform-type (TLP-type) floating offshore wind turbine (FOWT) against the extra buoyancy of FOWT. Therefore, the TLP-type FOWT will face the risk of tension leg failure. However, there are seldom analyses on the hydrodynamic response and tension leg failure performance of FOWT with inclined tension legs. In this paper, a hydrodynamic model was established using three-dimensional hydrodynamic theory and applied in the motion response and tension anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…It was found that for an inclined-tensioned TLP FOWT, when two or more tendons fail, there is a risk of collapsing [41][42][43]. The research pointed out that the mooring system should be carefully optimized to sustain the ability to withstand environmental loads under the failure condition.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that for an inclined-tensioned TLP FOWT, when two or more tendons fail, there is a risk of collapsing [41][42][43]. The research pointed out that the mooring system should be carefully optimized to sustain the ability to withstand environmental loads under the failure condition.…”
Section: Introductionmentioning
confidence: 99%